Deaths from land transport accidents in a city from Northwestern Paraná - Brazil - Lima, Meiri Vanderlei Nogueira de (2014)
Introduction: problems related to traffic accidents are not only attributes of large cities but also affect small and mid-sized towns. Objective: to describe the characteristics of deaths by land transport accidents in Cianorte-PR, from years 2000 to 2010. Methods: this was a descriptive study. The instrument used for data collection were the death certificates obtained from the Mortality Information System (MIS), including deaths in categories V01-V89 ICD-10 Chapter XX. Results: we studied 224 deaths. In 2010, the highest mortality rate was registered (45.7 / 100,000 inhabitants) and the lowest was in 2008 (16.7 / 100,000 inhabitants). Men were 79% (n = 177) of the victims and the sex ratio was 3.7:1. The highest proportion of deaths were in the group of 20-39 years (n = 95; 42%). Motorcyclists, cyclists and pedestrians are the most vulnerable, accounting for 57% (n=127). Among the deaths, 59% (n = 132) occurred at the scene. Deaths occurred predominantly on highways (n = 139; 62%), at the time from 6pm to 12am (n = 45; 34.1%) and on weekends (n = 70; 54%). Conclusion: land transport accidents are a current health issue for this population. More than half of the deaths are of young male adults. Seniors were also vulnerable. Intersectoral and multidisciplinary intervention strategies are strongly placed in the literature but, in everyday health services, they remain a challenge to be faced.